2015
DOI: 10.1093/jhered/esv073
|View full text |Cite
|
Sign up to set email alerts
|

Plastic and Evolved Responses to Global Change: What Can We Learn from Comparative Transcriptomics?: Table 1.

Abstract: Physiological plasticity and adaptive evolution may facilitate persistence in a changing environment. As a result, there is an interest in understanding species' capacities for plastic and evolved responses, and the mechanisms by which these responses occur. Transcriptome sequencing has become a powerful tool for addressing these questions, providing insight into otherwise unobserved effects of changing conditions on organismal physiology and variation in these effects among individuals and populations. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 130 publications
3
90
0
Order By: Relevance
“…Although the concentration and composition of these nutrients is well known to shape phytoplankton communities and influence physiological responses, the diversity of metabolic responses that underpin phenotypic changes in phytoplankton remains unknown in many cases. Gaining insight into these metabolic responses that drive phenotypic change can help define the physiological plasticity of organisms and their concomitant influence on marine food webs and carbon export (Azam et al, 1983; Longhurst and Glen Harrison, 1989; Ducklow et al, 2001; DeBiasse and Kelly, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Although the concentration and composition of these nutrients is well known to shape phytoplankton communities and influence physiological responses, the diversity of metabolic responses that underpin phenotypic changes in phytoplankton remains unknown in many cases. Gaining insight into these metabolic responses that drive phenotypic change can help define the physiological plasticity of organisms and their concomitant influence on marine food webs and carbon export (Azam et al, 1983; Longhurst and Glen Harrison, 1989; Ducklow et al, 2001; DeBiasse and Kelly, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Studies on multiple stressors have received increasing attention for their potential to reveal interesting information, which would be difficult to predict based on single stressor approaches (DeBiasse and Kelly, 2016;Gunderson et al, 2016), as well as to increase our understanding of responses to global change in natural multivariate environments (Hewitt et al, 2016). However, these approaches are still scarce in the literature and are mostly focused on the combined effects of temperature with other factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern is common for nonmodel species, and BLAST tools are known to fail for annotation of around 75% of the genes for de novo assemblies (Chiara et al, 2013; DeBiasse and Kelly, 2016). Gene ontologies indicated that the proportion of assembled genes associated with each functional category is similar between species, and that the de novo assemblies are comparable (Fig.…”
Section: Methods and Resultsmentioning
confidence: 99%